Financial Decisions and Reopening a Practice During the COVID-19 Pandemic: A Survey of California Plastic Surgeons. Issue 3 (May 2021) - Crowley, Jiwon Sarah; Reghunathan, Meera; Kadakia, Nikita; Barttelbort, Scott; Gosman, Amanda
Abstract : Background: On March 11, 2020, the World Health Organization declared COVID-19 as a global pandemic. As a response, the United States shut down public gatherings and businesses in an effort to quarantine. This included the stopping of elective operations, which greatly affected plastic surgeons and their practices during the initial shutdown. Objectives: We aim to study the early impact of COVID-19 on the financial implications and practice patterns of plastic surgeons in the state of California during the initial shutdown of elective surgery and provide guidelines for effective management during future crises. Methods: A 20-question survey was sent using Qualtrics XM software to 851 surgeon members of the California Society of Plastic Surgeons. The survey was open from May 13, 2020, to May 29, 2020. Standard statistical analysis was completed to compare private practice and nonprivate practice plastic surgeons. Results: We had a total of 140 respondents to our survey for a 16.5% response rate. The majority (77.1%) of the respondents were in a private practice setting. Private practice plastic surgeons reported a higher financial impact with a 79% reduction in financial income compared with nonprivate practice plastic surgeons at a 37% reduction ( P < 0.0001). Additionally, private practice plastic surgeons demonstrated a higher reduction in case volume and were more likely to lay off or furlough staff, close their practice, and apply for loans ( P < 0.001). Conclusions: Our survey study showed that private practice plastic surgeons in the state of California faced the most financial hardship during the early shutdown of the COVID-19 pandemic. It serves as a valuable snapshot in our economic history and depicts the heavy financial impact of the stopping of elective surgery. Since the reopening of practices, new guidelines have been implemented to maintain safe elective surgery while the pandemic continues. Further follow-up studies on both the state and national level need to be completed to see the continued financial effects on private and nonprivate plastic surgery practices since the reopening and resumption of elective surgery. Abstract : Supplemental digital content is available in the text.